2020
DOI: 10.1016/j.redox.2020.101651
|View full text |Cite
|
Sign up to set email alerts
|

NOX2 decoy peptides disrupt trauma-mediated neutrophil immunosuppression and protect against lethal peritonitis

Abstract: Trauma and sepsis are frequent causes of immunosuppression and risk of secondary bacterial infections and mortality among critically ill patients. Reduced activity of neutrophil NADPH oxidase 2 (NOX2) and impaired bacterial killing are among the major indices of immunosuppression. We hypothesize that NOX2-decoy peptides disrupt the inhibition of neutrophil NOX2 by plasma of patients with severe trauma and immunosuppression, thereby preserving the neutrophil respiratory burst that is a central antimicrobial mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Husain et al. ( 36 ) found that inhibiting CYBB could not only reduce neutrophil immunosuppression in critically ill patients with sepsis, but also reduce sepsis bacterial infection and organ damage, similar to the findings of our study. Inhibition of CYBB can also inhibit microglial activation and improve cognitive impairment after sepsis ( 37 ), as well as promoting sepsis myocardial injury through the ERK1/2-TNFα pathway ( 38 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Husain et al. ( 36 ) found that inhibiting CYBB could not only reduce neutrophil immunosuppression in critically ill patients with sepsis, but also reduce sepsis bacterial infection and organ damage, similar to the findings of our study. Inhibition of CYBB can also inhibit microglial activation and improve cognitive impairment after sepsis ( 37 ), as well as promoting sepsis myocardial injury through the ERK1/2-TNFα pathway ( 38 ).…”
Section: Discussionsupporting
confidence: 92%
“…Further, we used bioinformatics analysis to predict that elevated CYBB will lead to increased mPTP, thereby increasing NETs. Husain et al (36) found that inhibiting CYBB could not only reduce neutrophil immunosuppression in critically ill patients with sepsis, but also reduce sepsis bacterial…”
Section: Discussionmentioning
confidence: 99%
“…Male C57BL/6 mice and C57BL/6 Park2 −/− mice were purchased from The Jackson Laboratory (Bar Harbor, ME). Mice were given food and water ad libitum and kept on a 12-h light–dark cycle 26 , 27 . Mice 10 to 12 weeks of age were used for primary neutrophils and macrophages as well as to conduct experiments with metformin and sepsis-induced immunosuppression/secondary bacterial lung infections.…”
Section: Methodsmentioning
confidence: 99%
“…[50][51][52][53] Indeed, our results suggest that HMGB1 is released in parallel to mitochondrial ROS formation. Recent studies indicate that oxidation of HMGB1 contributed to HMGB1 translocation and extracellular flux, 54 although we did not test HMGB1 posttranslational modifications. These finding support a possibility that CNIinduced mitochondrial ROS can promote HMGB1 oxidation and AJT release.…”
Section: Clinical Studies and Experimental Models Of Organ Injury Havementioning
confidence: 99%